Art through the ages / [filem jalur] - Playfair, D. V.; Halliwell, A. E. (London : Educational Productions, 1962)
Contents : 1. Medieval art : 6th century to 14th century -- 2.Dawning Renaissance and realism : 14th and 15th centuries -- 3. Renaissance, realism and mannerism : 16th century -- 4. The Barque :17th century -- 5. Painters of the Rococo : 18th century -- 6. Classicism, romanticism and realism : 19th century -- 7. Impressionism and pointillism : 19th century -- 8. Expressionism : 19th and 20th century -- 9. The pure paintings : 19th and 20th century -- 10.Cubism and surrealism : 20th century